The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1123/jsep.2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Going to the Gym or to the Movies?: Situated Decisions as a Functional Link Connecting Automatic and Reflective Evaluations of Exercise With Exercising Behavior

Abstract: The goal of the present paper is to propose a model for the study of automatic cognition and affect in exercise. We have chosen a dual-system approach to social information processing to investigate the hypothesis that situated decisions between behavioral alternatives form a functional link between automatic and reflective evaluations and the time spent on exercise. A new questionnaire is introduced to operationalize this link. A reaction-time-based evaluative priming task was used to test participants' autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…This suggests people based their descriptions of pleasantness on both affective and instrumental attitudes, although evidence suggests that affective attitudes may be more predictive of physical activity behavior (Lowe et al, 2002; Rhodes et al, 2009). Most studies testing automatic evaluations of physical activity used generic positive/negative words and so were not similar to the stimuli produced from the present study (Calitri et al, 2009; Conroy et al, 2010; Hyde et al, 2010; Berry et al, 2011; Rebar et al, 2015a), but see Bluemke et al (2010) and Brand and Schweizer (2015) for activity-based stimuli in German. The findings of Bluemke et al (2010) suggest measures of automatic evaluations may be more linked to physical activity behavior if the adjective stimuli used are activity-related words; the outcomes of the present study make those types of stimuli more readily available for future researchers wishing to measure automatic evaluations.…”
Section: Discussionmentioning
confidence: 62%
“…This suggests people based their descriptions of pleasantness on both affective and instrumental attitudes, although evidence suggests that affective attitudes may be more predictive of physical activity behavior (Lowe et al, 2002; Rhodes et al, 2009). Most studies testing automatic evaluations of physical activity used generic positive/negative words and so were not similar to the stimuli produced from the present study (Calitri et al, 2009; Conroy et al, 2010; Hyde et al, 2010; Berry et al, 2011; Rebar et al, 2015a), but see Bluemke et al (2010) and Brand and Schweizer (2015) for activity-based stimuli in German. The findings of Bluemke et al (2010) suggest measures of automatic evaluations may be more linked to physical activity behavior if the adjective stimuli used are activity-related words; the outcomes of the present study make those types of stimuli more readily available for future researchers wishing to measure automatic evaluations.…”
Section: Discussionmentioning
confidence: 62%
“…This article refines earlier work on the significance of exercise-related affect for exercise motivation (e. g., Ekkekakis & Dafermos, 2012) and the role that automatic evaluations of exercise play in exercise-related decision-making and behavior (e. g., Brand & Schweizer, 2015). The article then introduces the Affective-Reflective Theory (ART) of physical inactivity and exercise, which focuses on the implications of momentary affective evaluations for exercise-related actions and choices.…”
Section: The Imperative To Expand Theoretical Horizons In Exercise Psmentioning
confidence: 91%
“…The theory focuses on the psychological processes that govern momentary behavior and deals specifically with exercise-related feelings; it emphasizes the concept of situated decisions about exercise (Brand & Schweizer, 2015) and consequences for behavior change.…”
mentioning
confidence: 99%
“…Sixteen studies were designed to investigate automatic affective processes. Six studies examined the differences in automatic affective reactions to stimuli associated with physical activity between physically active and inactive individuals [92][93][94][95][96][97]. Five of these studies showed the expected associations between automatic affective reactions and physical activity, but the effects sizes were highly variables (see table 1).…”
Section: Automatic Affective Processesmentioning
confidence: 99%
“…Sixteen studies were designed to investigate automatic affective processes. Individuals with higher levels of physical activity showed more positive automatic affective reactions toward active behaviors compared to individuals with lower levels of physical activity [80][81][82][83][84][85][86]. For example, Bluemke and collaborators [82] used a priming task in which exercise (e.g., to swim, to jog) or control (e.g., to read, to eat) verbs were presented before participants had to quickly categorize positive (e.g., athletic, strong) and negative (e.g., exhausted, tense) target words.…”
Section: Automatic Affective Processesmentioning
confidence: 99%